KEWENANGAN PEMERINTAH DAERAH DALAM PENGAWASAN PROSES PRODUKSI, PENGOLAHAN, DAN DISTRIBUSI HASIL PERIKANAN (Studi Kasus Di Kabupaten Donggala) - Assagaf, Ali; Kasim, Aminuddin; Surachman; As Syifa Ulchairan (JURNAL RISET INDRAGIRI, 2023)
This research aims to conduct a comprehensive analysis of the local government's authority in the fisheries sector in Donggala Regency. Additionally, it aims to formulate the division of authority between the local government of the regency and the province in overseeing the production, processing, and distribution of fishery products in Donggala. The governance is based on the principle of support duties in the marine and fisheries sector, operationalized through various Minister of Marine Affairs and Fisheries regulations (PERMEN-KP) as a follow-up to Law Number 45 of 2009 concerning Fisheries. This is reinforced by Law Number 23 of 2014 concerning Regional Government, governing the supervision of the production, processing, and distribution of fishery products. Nevertheless, there is still varied interpretation of the terminology of Fish Auction Places (TPI) and the origin information services for fish from fishery production centers. The research method employed is normative legal research combined with field data collection. Legal and conceptual approaches are applied to discuss the local government's authority in overseeing the production, processing, and distribution of fishery products, with Donggala Regency as a case study. Amendments to articles in PERMEN-KP regulating the management of TPI and the distribution of fishery products are deemed necessary. These amendments can assign a role to regencies/cities in the management and organization of (TPI) and the legality of the origin of fish within the jurisdiction of regencies/cities, reflecting the implementation of the autonomy principle and support duties. Keywords: Fisheries Sector, Fish Auction Places, Local Government Authority, Fish Production Process Supervision